Can we find a trace of the Islamic Law in the christian arabe documents of Toledo of the XIIth and XIIIth centuries? - Molénat, Jean-Pierre (2016)
During the 12th and 13th centuries, Toledo´s notarial diplomas certify the persistent Arabization of city Christian populations, traditionally designated as Mozarabic. Not only the script and the and the language of those diplomas are effectively Arabic, but also the used formulas, starting by the initial basmala (God´s invocation), have the origin in the Muslim notarial practice. The featured witnesses are “professional witnesses”, and here one is able to find some of the city’s prominent personalities, who certify have seen and heard both parties establish the contract. That said, the contract celebration is situated in a recent past, and not in the present, as it occurs with the notarial acts form the non-Arab Christian population from the same period. Yet, over and above the formal issues, it is not easy to find a direct influence of the Islamic law in those diplomas. Even an expression of Arab origin as evident as «marjadraque» [marǧi‘al-darak] it does not necessarily addresses to any Islamic law rule, as that guarantee was already assured in the Visigoths’ law. Also, the clauses of the matrimonial contracts or family shares, are more as per the Fuero Juzgo than the Islamic law. Although the enormous Arab influence in the “Mozarabic Christians” from Toledo, which actually lasted more than two centuries after city´s Christian conquer, it is not possible to find testimonies that prove the influence of the Islamic law over them.   Bibliography Sources Al-MaqSad al-maḥmūd fī talḫīṣ al-‘uqūd (Proyecto plausible de compendio de formulas notariales). Ed. Asunción Ferreras. Madrid: CSIC (Fuentes Arábico-Hispanas 23), 1998. Al-Mudawwana l-kubrā. Ed. Dār Ṣādir. Beyrouth: s.l., s. d. Al-Kāfī fī fiqh ahl al-Madīna al-mālikī. Ed. anonyme. Beyrouth: Dār al-Kutub al-‘Ilmiyya, 2e ed., 1413 H/ 1992. Al-Muqni‘ fī ‘ilm al-šurūṭ (Formulario notarial). Ed. Francisco Javier Aguirre Sábada. Madrid: CSIC (Fuentes Arábico-Hispanas 5), 1994. COLECCIÓN de fueros municipales y cartas pueblas de los reinos de Castilla, León, Corona de Aragón y Navarra. Ed. Tomás Muñoz y Romero. Madrid: Imprenta de Don José María Alonso, 1847 (réimp. fac-similé, Madrid, 1979). COLECCIÓN diplomática del monasterio de Carrizo, t. 1 (969-1260). Ed. María Concepción Casado Lobato. León: Centro de Estudios y Investigación San Isidoro, 1983. CRÓNICA del rey don Pedro y del rey don Enrique. Ed. Germán Orduna. Buenos Aires: Secrit, 1994. EL CORÁN de Toledo. Edición y estudio del manuscrito 235 de la Biblioteca de Castilla-La Mancha. Ed. C. López-Morillas. Gijón: Trea, 2011. HISTORIA DE LOS HECHOS de España. Ed. Juan Fernández Valverde. Madrid: Alianza, 1989. Kitāb al-waṯā’iq wa-l-siǧillāt. Formulario notarial hispano-árabe por el alfaquí y notario cordobés Ibn al‑‘Aṭṭār (s. X). Ed. Pedro Chalmeta et Federico Corriente. Madrid: Academia matritense del notariado, 1983. LOS CARTULARIOS de Toledo. Catálogo documental. Ed. Francisco J. Hernández. Madrid: Fundación Ramón Areces, 1985. Rāġib, Yūsuf – Actes de vente d'esclaves et d'animaux d'Égypte médiévale 2. Le Caire: Institut français d'archéologie orientale, 2006. SUMARIO de la relación y ejercicio espiritual sacado y declarado por el Mancebo de Arévalo en nuestra lengua castellana. Ed. Gregorio Fonseca Antuña. Madrid: Trea, 2002. TRATADO [Tafsira] Mancebo de Arévalo. Ed. María Teresa Narváez Córdoba. Madrid: Trotta, 2003.   Studies BEARMAN, J. P ; BIANQUIS, Th.; BOSWORTH, C. E.; VAN DONZEL, E.; HEINRICHS, W. P. (eds.) – Encyclopédie de l'Islam. 2e ed., t. 6. Leiden: Brill, 1991. CAHEN, Claude – "A propos des shuhūd". Studia Islamica,n. 31 (1970), pp. 71-79. CARRASCO, Rafael – Deportados en nombre de Dios. La expulsión de los moriscos: cuarto centenario de una ignominia. Barcelone: Ediciones Destino, 2009. CERVERA, María José – "Documento árabe de venta (Zaragoza, 1194) ". Estudios de dialectología norteafriacana y andalusí, n.2 (1997), pp. 83-93. CORRIENTE, Federico – Diccionario de arabismos y voces afines en iberorromance. Madrid: Gredos, 1999. DICTIONNAIRE des orientalistes de langue française. Dir. François Pouillon. Paris: IISMM-Karthala, 2008. ECHEVARRÍA, Ana; MAYOR, Rafael – "Las actas de reunión de una cofradía islámica de Toledo. Una fuente árabe para el estudio de los mudéjares castellanos. Años 1402 a 1414". Boletín de la Real Academia de la Historia, n.207/2 (2010), pp. 257-293. FERRANDO FRUTOS, Ignacio – El dialecto andalusí de la Marca Media. Los documento mozárabes de los siglos XII y XIII. Saragosse: Universidad de Zaragoza, 1995. FERRANDO FRUTOS, Ignacio – "Los romancismos de los documentos mozárabes de Toledo". Anaquel de Estudios Árabes, n.6 (1995), pp. 71-86. FITA, Fidel – "Marjadraque según el Fuero de Toledo". Boletín de la Real Academia de la Historia, n.7 (1885), pp. 360-394. GARCÍA-ARENAL, Mercedes – "Documentos árabes de Tudela y Tarazona". Al-Qanṭara, n.3 (1982), pp. 27-72. GARCÍA-ARENAL, Mercedes; WIEGERS, Gerard (eds.) – Los moriscos: expulsión y diáspora. Una perspectiva internacional. Valence: Prensas de la Universidad de Zaragoza, 2013. GARCÍA DE VALDEAVELLANO, Luis – "La cuota de libre disposición en el derecho hereditario de León y Castilla en la alta Edad Media". Anuario de Historia del Derecho Español, n.9 (1932), pp. 129-176. – Estudios medievales de derecho privado. Séville: Universidad de Sevilla, 1977. GARCÍA GALLO, Antonio – "Los Fueros de Toledo". Anuario de Historia del Derecho Español,n. 45 (1975), pp. 341-488. GARCÍA MORENO, Luis A. – "Orgullo de estirpe: la nobleza cordobesa en el 615 A.D." Mainake, n. 31 (2009), pp. 115-122. GARCÍA ULECIA, Alberto – "El regimen económico del matrimonio en los derechos locales leoneses". Historia. Instituciones. Documentos, n. 9 (1982), pp. 165-197. GONZÁLEZ, Julio – El reino de Castilla en la época de Alfonso VIII. III – Documentos (1191-1217). Madrid: Consejo Superior de Investigaciones Científicas – Escuela de Estudios Medievales, 1960. – Repoblación de Castilla la Nueva. Madrid: Universidad Complutense, Facultad de Filosofía y Letras, 1975. GONZÁLEZ PALENCIA, Ángel – Los Mozárabes de Toledo en los siglos XII y XIII. Madrid: Instituto de Valencia de Don Juan, 1926-1930. GUICHARD, Pierre; MOLÉNAT, Jean-Pierre – "Dans al-Andalus, les ulémas face aux chrétiens". in BAZZANA, André; BÉRIOU, Nicole; GUICHARD, Pierre (eds.) – Averroès et l’averroïsme. Un itinéraire historique du Haut Atlas à Paris et à Padoue. Lyon: Presses Universitaires de Lyon, 2005, pp. 191-200. HERNÁNDEZ, Francisco J.; LINEHAN, Peter – The mozarabic Cardenal. The Life and Times of Gonzalo Pérez Gudiel. Florence: Edizioni del Galluzzo, 2004. HOENERBACH, Wilhelm – Spanisch-Islamische Urkunden aus der Zeit der Naßriden und Moriscos, Berkeley-Los Angeles: University of California Press, 1965. LOMAS CORTÉS, Manuel – El puerto de Dénia y el destierro morisco (1609-1610). Valence: Universidad de Valencia, 2009. LUZ ALONSO, María – "La perduración del Fuero Juzgo y el derecho de los castellanos de Toledo". Anuario de Historia del Derecho Español, n. 48 (1978), pp. 335-377. – "La dote en los documentos toledanos de los siglos XII-XV". Anuario de Historia del Derecho Español, n. 48 (1978), pp. 379-456. – "La compraventa en los documentos toledanos de los siglos XII-XV". Anuario de Historia del Dercho Español, n.49 (1979), pp. 455-517. – "La succesión mortis causa en los documentos toledanos de los siglos XII-XV". Anuario de Historia del Dercho Español, n. 50 (1980), pp. 941-970. MERÊA, Paulo – "O dote visigótico". in Estudos de Direito visigótico. Coïmbre: Universidade de Coimbra, 1948. – "Sobre as origens do executor testamentário". in Estudos de Direito Hispânico Medieval. Coïmbre: Universidade de Coimbra, 1953. MOLÉNAT, Jean-Pierre – "La volonté de durer: majorats et chapellenies dans la pratique tolédane des XIIIe-XVe siècles". En la España Medieval, n.5(Madrid, 1986), pp. 683-696. – "L'arabe à Tolède, du XIIe au XVIe siècle". Al-Qanṭara, n.15 (1994) pp. 473-496. – "Le problème du rôle des notaires mozarabes dans l'œuvre des traducteurs de Tolède, XIIe-XIIIe siècle". La España Medieval, n.18 (1995), pp. 29-60. – Campagnes et Monts de Tolède du XIIe au XVe siècle. Madrid: Casa de Velázquez, 1997. Thèse de doctorat d’État. – "Sur le rôle des Almohades dans la fin du christianisme local au Maghreb et en al-Andalus". Al-Qanṭara,n. 18/2 (Madrid, 1997), pp. 389-413. – "Y a-t-il eu des mozarabes à Tolède du VIIIe au XIe siècle?". in Entre el califato y la taifa: Mil años del Cristo de la Luz (Actas del Congreso Internacional, Toledo, 1999). Tolède: Asociación de Amigos del Toledo Islámico, 2000, pp. 97-106. – "L'identité mozarabe dans l'Ibérie reconquise, spécialement à Tolède". in BRESC, Henri; VEAUVY, Christiane (dir.) – Mutations d'identités en Méditerranée. Moyen Âge et Époque contemporaine. Saint-Denis: Ed. Bouchene, 2000, pp. 123-131. – "Tolède vue par les chroniqueurs Rodrigo Jiménez de Rada et Pero López de Ayala, rapprochés de leurs prédécesseurs de langue arabe, latine ou romane". Mélanges de la Casa de Velázquez – Nouvelle série, n. 44/1, 2014, pp. 179-197. RIVERA RECIO, Juan Francisco – La Iglesia de Toledo en el siglo XII. Vol. 1. Rome: Publicaciones del Instituto Español de Historia Eclesiastica, 1966. RODRÍGUEZ GÓMEZ, Maria Dolores; DOMÍNGUEZ ROJAS, Salud María – "La compraventa de fincas urbanas en la Granada del siglo XV a través de dos documentos notariales árabes". Anaquel de Estudios Árabes, n.19 (2008), pp. 175-199). SCHACHT, J. – "Waṣīya". in HOUTSMA, M. Th.; BASSET, R.; ARNOLD, T. W (ed.) - Encyclopédie del Islam. 1er ed., t. 4. Leiden: Brill et Picard, 1934. TYAN, Émile – Le notariat et le régime de la preuve par écrit dans la pratique du droit musulman. Harissa: Annales de l'École française de droit de Beyrouth, 1945.